Politics Law On Notary Provision Obligation to Implement Principles for Recognizing User Services (PMPJ) - Hasrul Hasrul; Maryanto Maryanto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
This study aimed (1) to determine the relevant arrangements Principle Recognizing User Services, (2) To know the laws granting political liability to the Notary to apply the principle Recognizing User Services.This type of research used by the author is a normative law research. The type of approach used is the approach of law (statute approach), then analyzed using descriptive qualitative analysis.This research resulted in (1) the enactment of Act No. 10 of 2010 on the Prevention and Combating of offense of Money Laundering and Act No. 9 of 2013 on the Prevention and Eradication of the Financing of Terrorism, is a cornerstone of the principal legal for the application of the principle of Identifying Users services and reinforced by Government Regulation No. 43 Of 2015 on the Reporting Parties under the Prevention and Combating of Money Laundering. (2) Political granting legal obligation to apply the principle to the Notary Recognizing User Services is to assist governments to combat money laundering. This is because it turns out in addition to utilizing the financial institution, the money launderers also use certain professions in which the relationship between the professional and his client confidentiality is protected by law or code of conduct.Keyword: Liability Notary; Money Laundering; Principles Recognizing User Services (PMPJ).